Legal Analysis Of Divorce Law That Was Rejected By The Judges On The Reasons Of Discussion and Archipelago (Decision Study No.1257/Pdt.G/2021/PN.SBY) - Hotmarganda Tua Sihombing; Suhaila Zulkifli; Tajuddin Noor (Jurnal Mamangan, 2022)
In the 1970s the government of the Republic of Indonesia issued regulations governing marriage, namely Law No. 1 of 1974 concerning marriage. Marriage is an important part of human life and is sacred. Divorce is the decision or loss of husband and wife status between a man and a woman by a court that has the authority to decide it. But of course in a divorce also has conditions for couples who want to file for divorce against their partners. This research uses the normative legal research method, in which the normative research method is carried out by examining literature or literature. The divorce mechanism is regulated in Government Regulation No. 9 of 1975, which in the PP states that a couple who wishes to divorce in filing a lawsuit must first know which court is authorized to do so, if the Muslim is in the Religious Court, then other than Islam then in the Court. Country. A couple who wants to file for divorce must of course first understand the mechanism for divorce and the conditions for divorce which include the reasons, that everyone who wants a divorce must have strong reasons in which the reasons are no longer able to lead a good household life. . This is found in Article 39 of the Marriage Law. If it is related to the study of the decision No.1257.Pdt.G/2021/PN.Sby the judge considered that the plaintiff failed to prove the argument for his lawsuit by failing to bring the right witnesses to prove the argument for his trial, the plaintiff only presented his family as witnesses which according to the judge it is a unilateral statement which will only benefit the plaintiff's position, so that in the verdict the judge rejects the plaintiff's claim in its entirety.